Low birth weight causes insulin resistance and aberrant intestinal lipid metabolism independent of microbiota abundance in Landrace–Large White pigs. Issue 8 (30th May 2019) - Fontaine, Melanie A.; Diane, Abdoulaye; Singh, Vijay P.; Mangat, Rabban; Krysa, Jacqueline A.; Nelson, Randy; Willing, Benjamin P.; Proctor, Spencer D.
ABSTRACT: Low birth weight (LBW) and postnatal nutrition are risk factors for adult metabolic diseases. However, the interactions between LBW, diet, and intestinal lipid absorption and secretion leading to adult metabolic disease remain unclear. The current study determined the impact of LBW on intestinal lipid and carbohydrate metabolism under both control and Western diet (high fat, high fructose, and cholesterol) conditions in 5‐wk‐old LBW and normal birth weight (NBW) Landrace–Large White × Duroc pigs. A 2‐step modified oral glucose and fat challenge test was performed. Mesenteric lymph, jejunal mucosal scrapings, and cecal digesta samples were also collected. LBW offspring were lower in weight and gained less weight per day. LBW pigs on either control or Western diets displayed increased triglyceride (TG) secretion into lymph ( P = 0.0135). Western diet‐fed LBW pigs developed fasting ( P = 0.03) and postprandial ( P < 0.05) hypertriglyceridemia, muscle steatosis ( P = 0.0072), had higher insulin excursion ( P < 0.01), increased jejunal stearoyl‐CoA desaturase 1 mRNA and increased hepatic fibrosis ( P = 0.0017) compared with NBW piglets. Gut microbiota showed significant dysbiosis on Western diet independent of birth weight. In conclusion, LBW pigs fed a Western diet specifically up‐regulate TG absorption and secretion, develop dyslipidemia, muscular steatosis, and display early signs of insulin resistance. Interestingly, this study does not provide evidence of altered intestinal microbiome in LBW pigs contributing to increased severity of metabolic diseases.—Fontaine, M. A., Diane, A., Singh, V. P., Mangat, R., Krysa, J. A., Nelson, R., Willing, B. P., Proctor, S. D. Low birth weight causes insulin resistance and aberrant intestinal lipid metabolism independent of microbiota abundance in Landrace‐Large White pigs. FASEB J. 33, 9250–9262 (2019). www.fasebj.org